2005
DOI: 10.1093/brain/awh540
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial changes in skeletal muscle in amyotrophic lateral sclerosis and other neurogenic atrophies

Abstract: Previous findings suggested specific mitochondrial dysfunction in skeletal muscle of patients with amyotrophic lateral sclerosis (ALS). To answer the question of whether the dysfunction is specific, we investigated the histochemical distribution of mitochondrial marker activities, the ratio of mitochondrial (mt) versus nuclear (n) DNA, and the activities of citrate synthase (CS) and respiratory chain enzymes in muscle biopsies of 24 patients with sporadic ALS. The data were compared with those in 23 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
43
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 26 publications
9
43
0
1
Order By: Relevance
“…We and others had previously shown mitochondrial dysfunction accompanied by ATP depletion and uncoupling protein 3 upregulation in skeletal muscle of mSOD1 mice (16) and ALS patients (28)(29)(30)(31). It is thus probable that this mitochondrial impairment could underlie the increased energy needs of skeletal muscle, as reflected by the increased rates of glucose uptake (6) and TG clearance shown here.…”
Section: Discussionsupporting
confidence: 57%
“…We and others had previously shown mitochondrial dysfunction accompanied by ATP depletion and uncoupling protein 3 upregulation in skeletal muscle of mSOD1 mice (16) and ALS patients (28)(29)(30)(31). It is thus probable that this mitochondrial impairment could underlie the increased energy needs of skeletal muscle, as reflected by the increased rates of glucose uptake (6) and TG clearance shown here.…”
Section: Discussionsupporting
confidence: 57%
“…*, p Ͻ 0.05; **, p Ͻ 0.01. E, oxygen consumption rates of the myotubes were analyzed on day 7 in the absence (Basal) or presence of 2.5 g/ml oligomycin (Oligo) and a 1. by atrophy and mitochondrial dysfunction (66,67). PERM1 followed a similar pattern of induction by exercise and suppression in ALS patients, suggesting that the regulatory pathways seen in C2C12 cells reflect ones that are active in human exercise physiology and in the pathophysiology of neuromuscular disorders.…”
Section: Discussionmentioning
confidence: 85%
“…Many ALS patients are hypermetabolic, an early and persistent phenomenon (Bouteloup et al, 2009, Desport et al, 2005. Muscular mitochondrial function in amyotrophic lateral sclerosis is progressively altered in ALS patients (Echaniz-Laguna et al, 2006, Krasnianski et al, 2005, and subtle ultrastructural changes of hepatocytes and liver dysfunction have also been described in biopsy specimens from ALS patients (Nakano et al, 1987). Significant changes were also found in skeletal muscle mitochondria of transgenic SOD1 (tgSOD1) animals (Dupuis et al, 2009, Krasnianski et al, 2005.…”
Section: General Characterization Of Mitochondria In Alsmentioning
confidence: 99%
“…Muscular mitochondrial function in amyotrophic lateral sclerosis is progressively altered in ALS patients (Echaniz-Laguna et al, 2006, Krasnianski et al, 2005, and subtle ultrastructural changes of hepatocytes and liver dysfunction have also been described in biopsy specimens from ALS patients (Nakano et al, 1987). Significant changes were also found in skeletal muscle mitochondria of transgenic SOD1 (tgSOD1) animals (Dupuis et al, 2009, Krasnianski et al, 2005. It was suggested that increased ROS generation by skeletal muscle mitochondria (Muller et al, 2007) or mitochondrial uncoupling (Dupuis et al, 2009) may be primarily responsible for the loss of neuromuscular junctions and secondary distal degeneration of motor neurons in SOD1 mice.…”
Section: General Characterization Of Mitochondria In Alsmentioning
confidence: 99%